The impact of institutional factors on the performance of genuine savings. Issue 1 (2nd January 2018) - Sato, Masayuki; Samreth, Sovannroeun; Sasaki, Kengo
ABSTRACT: This study investigates institutional factors affecting the performance of genuine savings (GS), which are often used in assessing sustainable development, and adopts a model of autoregressive conditional heteroscedasticity in mean. We pay particular attention to the contribution of institutions to decrease the volatility level of the GS path. The estimation results show that there are two ways in which institutions affect GS performance. First, high quality of institutions enhances the GS level directly. Second, high quality of institutions enhances the GS level via stabilizing the volatility of the GS path. Considering both effects in their totality, institutional improvement plays an important role in realizing a sustainable development path.